Group IIC self-splicing intron-derived novel circular RNA vaccine elicits superior immune response against RSV - Sun, Zeyun; Lu, Lirong; Liu, Lijie; Liang, Ruoxu; Zhang, Qiqi; Liu, Zhining; An, Jiahao; Liu, Qian; Wu, Qingxin; Wei, Shuai; Zhang, Long; Peng, Wei (Frontiers in Immunology, 2025)
IntroductionThe remarkable commercial success of mRNA vaccines against COVID-19 and tumors, along with their potential as therapeutic drugs, has significantly boosted enthusiasm for circular RNAs (circRNA) as a promising next-generation therapeutic platform. The development of novel circRNA cyclization technologies represents a significant leap forward in RNA engineering and therapeutic applications. Recent advancements in group I and IIB self-splicing intron-based ribozymes have enabled precise cyclization of RNA molecules. However, this approach faces significant limitations, including low cyclization efficiency and the requirement for additional additives, which restrict its broader application. Group IIC self-splicing introns represent the shortest known selfsplicing ribozymes and employ a splicing mechanism that is fundamentally distinct from that of group IIB self-splicing introns. However, the potential of group IIC self-splicing introns to carry exogenous sequences for the development of circular RNA-based platforms remains an open question and warrants further investigation.MethodsHere, we demonstrate that group IIC self-splicing introns can efficiently circularize and express exogenous proteins of varying lengths, as evidenced by luciferase and GFP reporter systems. Leveraging structural biology-based design, we engineered the RSV pre-F protein and validated the potential of IIC self-splicing introns as a vaccine platform for preventing infectious diseases.ResultsIn mouse models, the novel nucleic acid vaccine developed using IIC self-splicing introns elicited superior immunogenicity and in vivo protective efficacy compared to protein-adjuvant vaccines.DiscussionThe development of the novel circular RNA vaccine platform holds significant promise for advancing next-generation therapeutics for disease treatment and prevention.